β-Lactam Antibiotics—Drug-Drug Interaction Mediated by Organic Anion Transporters OAT1 and OAT3 - I. A. Mazerkina; V. A. Evteev; A. B. Prokofiev; O. V. Muslimova; E. Yu. Demchenkova (Регуляторные исследования и экспертиза лекарственных средств, 2020)
Organic anion transporters OAT1 and OAT3 play a key role in elimination of most β-lactam antibiotics. Since nonsteroidal anti-inflammatory drugs, antivirals, antitumor agents, and some other drugs are also substrates of OAT1/3, this enables drug-drug interaction (DDI). The aim of the study was to analyze scientific literature to determine the likelihood and significance of β-lactam antibiotic DDI mediated by organic anion transporters, as well as potential for predicting it. In clinical practice, inhibition of β-lactam antibiotic elimination is used to increase systemic exposition and reduce the cost of antibiotic therapy. OAT inhibitors (cilastatin, betamipron) are used in combination drugs to reduce nephrotoxicity of carbapenems. On the other hand, an increase in the concentration of β-lactams due to OAT inhibition may lead to adverse drug reactions. Therefore, the European Medicines Agency and the Food and Drug Administration recommendations for the development of new drugs state that in the case of significant renal excretion (≥25%) it is necessary to investigate OAT1/3 transport in vitro and calculate inhibition constant Ki and/or half maximal inhibitory concentration IC50 for predicting DDI. One of the main problems is the variability of Ki and IC50 values between laboratories, which requires the development of general recommendations for different transporters as regards methods of determination of these parameters.